Efficiency determinants of Malaysian public Waqf in a dynamic environment / Hazriah Hasan - Hasan, Hazriah (2016)
Managerial efficiency is all important in financing a not-for-profit foundation. Waqf or endowment is among one of the Islamic financial institutions set up for the sole intention to serve as a catalyst for economic growth and development of Muslims. In Malaysia, every state does its own Waqf department under the organization of State Islamic Religion Councils (SIRCs). As sole single trustees of Waqf funds, SIRCs are responsible to do all the bodily processes and transactions done for the development and aggregation of finances as easily as to invest and administer the revenues from the finances. This research is divided into three analyses. Firstly, this research did an extensive measurement using the Data Envelopment Analysis (DEA) to investigate the dynamic efficiency performance of Waqf Departments in Malaysia.